CORPORATE MANAGEMENT IN THE SYSTEM TO MINIMIZE THE RISKS OF INTERNAL CONFLICTS - M. G. Sukhorukova (Модернизация, инновация, развитие, 2016)
In recent years the practice of the corporate confl icts infl uences harmfully the enterprise activities. The corporate confl icts are one of the modern forms of contradictions in the company. In the conditions of the developing economy and the growing market, it is important to fi nd the ways of minimization of the corporate contradictions. The actuality of this subject is also connected with imperfection of legislative base and insuffi ciency of the developed strategy in the fi eld of corporate management. Special practice about minimization of the corporate confl icts is not popular in the Russian companies. Process of corporate management is investigated in this article as a base of internal confl icts minimization. The purpose is а substantiation of the importance of corporate management as a base of risk minimization in the enterprise and identifi cation of the ways how to improve the corporate management in Russia. The practical importance is a possibility to improve the system of confl icts minimization by strengthening and supporting of the high level of corporate management.